Implementasi Pemberdayaan Ekonomi Mustahik Melalui Program Z-Mart Baznas Kabupaten Siak (Studi Pada Penerima Program Z-Mart Kecamatan Siak - Ali, Sri Indriyani (EL-EMIR Institute, 2025)
This thesis is entitled Implementation of Mustahik Economic Empowerment Through the Z-Mart Program of Baznas Siak Regency (Study on Z-Mart Program Recipients in Siak District). With the aim of analyzing and knowing how the implementation of the Z-Mart program from BAZNAS Siak Regency empowers the Mustahik economy in Siak District, The research method used is a qualitative research method with data collection techniques through interviews, observation, and documentation. The results showed that the implementation of the Z-Mart program has several stages, including the introduction stage, assessment stage, acceptance stage, assistance stage, and evaluation. However, in its implementation, there are several obstacles, such as distributors whose management is not running smoothly, the emergence of retail business competition such as Indomaret and Alfamart, and mentoring that has not been optimal. This study recommends several suggestions to increase its effectiveness in empowering the Mustahik economy